2012
DOI: 10.1128/jcm.05392-11
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Transmission in a Country with Low Tuberculosis Incidence: Role of Immigration and HIV Infection

Abstract: Immigrants from high-burden countries and HIV-coinfected individuals are risk groups for tuberculosis (TB) in countries with low TB incidence. Therefore, we studied their role in transmission of Mycobacterium tuberculosis in Switzerland. We included all TB patients from the Swiss HIV Cohort and a sample of patients from the national TB registry. We identified molecular clusters by spoligotyping and mycobacterial interspersed repetitive-unit-variable-number tandem-repeat (MIRU-VNTR) analysis and used weighted l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
51
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 28 publications
8
51
2
Order By: Relevance
“…The predominance of Euro-American lineage finding (also known as linage 4) in this study also similar with the reports of previous studies, reported as the dominant lineage in different regions of Ethiopia (Diriba et al, 2013;Firdessa et al, 2013;Tessema et al, 2013). In a study conducted in Switzerland, the Euro-American and Indo-Oceaninc linage proportion were 72.7 and 8.3% which are higher and lower respectively compared to the present study result (Fenner et al, 2012). In another study conducted in USA, the Euro-American linage prevalence was lower than the present finding which was 13.8% while, the Indo-Oceanic prevalence in this study was lower as compared to 22.6% (Eleanor et al, 2012).…”
Section: Strain Characterizationsupporting
confidence: 81%
“…The predominance of Euro-American lineage finding (also known as linage 4) in this study also similar with the reports of previous studies, reported as the dominant lineage in different regions of Ethiopia (Diriba et al, 2013;Firdessa et al, 2013;Tessema et al, 2013). In a study conducted in Switzerland, the Euro-American and Indo-Oceaninc linage proportion were 72.7 and 8.3% which are higher and lower respectively compared to the present study result (Fenner et al, 2012). In another study conducted in USA, the Euro-American linage prevalence was lower than the present finding which was 13.8% while, the Indo-Oceanic prevalence in this study was lower as compared to 22.6% (Eleanor et al, 2012).…”
Section: Strain Characterizationsupporting
confidence: 81%
“…In addition, we included a random sample of 288 TB patients from the 4,221 patients with culture-confirmed TB reported to the National TB Surveillance Registry, and all of the drug-resistant TB patients reported in Switzerland (n ϭ 167) during the same period (categories not mutually exclusive). Twenty-four-locus MIRU-VNTR typing and spoligotyping were used for the molecular detection of transmission clusters (9). In this follow-up study, we performed WGS of the 90 M. tuberculosis isolates belonging to 1 of the 35 MIRU-VNTR typing/spoligotyping clusters.…”
Section: Methodsmentioning
confidence: 99%
“…In 2012, we conducted a nationwide study of the molecular epidemiology of TB in Switzerland as a collaborative project involving the Swiss HIV Cohort Study (SHCS), the National Center for Mycobacteria, diagnostic microbiology laboratories, departments of respiratory medicine and public health, and the Federal Office of Public Health (www.tb-network.ch) (9,(25)(26)(27)(28). The study setting was previously described in detail (9). Briefly, all of the patients in the SHCS diagnosed with TB between 2000 and 2008 were enrolled (n ϭ 93).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations